Tooth dimensions and body size in a Pygmy population - Fernando V. Ramirez-Rozzi; Alejandro Romero (Annals of Human Biology, 2019)
Background: The relationship between tooth size and stature has been analysed extensively at the interspecies level but has received less attention at the intraspecies level. The relationship between these two parameters does not seem to be the same among modern human populations. Aim: The aim of this study is to analyse the relationship between tooth dimensions and body measurements in the Baka Pygmies. Subjects and methods: Height, weight, and tooth dimensions were obtained for 45 adult Baka females and 17 males from Le Bosquet (Cameroon). Correlations were obtained between the variables and compared to results for other human populations. Results: The Baka population is distinctive in the small number of significant correlations. Only two buccolingual diameters among Baka females show any significant correlation with height. The lack of significant correlations between tooth dimensions and body dimensions among the Baka means that changes in body size are accompanied by random variations in tooth dimensions. Conclusion: The absence of correlations may be accounted for by the impact of environmental effects on the somatic growth of the Baka producing a Pygmy phenotype adapted to live in the forest. It is worth noting that many correlations become significant when sexes are pooled.